Agenda Ambiental da Administração Pública e Objetivos do Desenvolvimento Sustentável: alinhamento para uma agenda aprimorada - Cezar, Fernando Vieira (2023)
The concern with sustainability and sustainable development comes from a significant time horizon. The Public Administration Environmental Agenda (A3P), created in 1999, and the 2030 Agenda, created in 2015 and which presents the Sustainable Development Goals (SDGs) are examples of important tools for sustainability. This work aims to identify how A3P can incorporate SDGs. For this, a qualitative research was carried out through interviews and documentary research. Of the 24 Federal Institutions of Higher Education (IFES) that adhere to the A3P, it was decided to choose one from each region, totaling 13 IFES studied. Of these, it was possible to conduct interviews with 5 responsible for the sustainability sector at the institution, and a documentary research was carried out with 9 IFES. The documentary research analyzed institutional documents that present information about the actions that the institution develops in favor of sustainability. The interviews, in addition to identifying these actions, covered the relationship between A3P and the SDGs and the creation of a new axis for A3P. As a result, an improved A3P was proposed in connection with the SDGs and with specific actions that universities can develop in favor of sustainability. This proposal was sent to experts who gave their opinion and contributions. A framework for integrating the SDGs with A3P was also proposed. In general, it was noticed that, for sustainability to really happen in practice, institutional engagement is needed, with a sector that is especially responsible for A3P and that actions are carried out at the macro level, which encompass all areas of knowledge to cover all training, providing students and the community with a sustainable collective awareness. It is also important that institutions take ownership of the SDGs as transversal. To think and promote A3P is to think and promote sustainability. To promote sustainability is to guarantee a better world for everyone, and this work contributes towards improving the A3P, which is an agenda for sustainability in public institutions.